Conventional Versus Biorational Insecticides for Controlling Mustard Aphid and Their Effects on Beneficial Insects (Journal of the Bangladesh Agricultural University, 2024)
Mustard is one of the most important oilseed crops in Bangladesh. However, its production is severely constrained by aphid infestation. Farmers usually spray conventional insecticides to control aphids that negatively affect beneficial insects and environment. Thus, alternatives to conventional insecticides are required. We tested three biorational insecticides (Nimbicidine @ 1ml/L, Spinosad: Libsen 45SC @ 0.5 ml/L and Lufenuron: Hayron 5EC @ 0.5ml/L of water) against aphid infestation and assessed their effect on ladybird beetle and honey bee and compared these effects with two conventional insecticides (Diazinon: Sabion 60EC @ 2ml/L and Cypermethrin: Cypraplus 10EC @ 1ml/L of water) and with an untreated control. The study was conducted in a randomized complete block design with each treatment replicated thrice in the field of Department of Entomology, Bangladesh Agricultural University. Number of infested plants per plot, aphid per plant and per pod, number of ladybird beetle and honey bee per plot was counted and yield per plot was calculated. All tested insecticides reduced aphid infestation compared to untreated control indicating all of them were effective against aphid. However, Lufenuron and Nimbicidine was most effective to reduce plant infestation and number of aphids per plant and pod. Spinosad and Sabion were found fairly effective whereas Cypraplus was found to be least effective. Lufenuron and Nimbicidine did not reduce the number of ladybird beetle and honey bee visit per plot, however, Spinosad and conventional insecticides reduced their number. Lufenuron treated plots provided highest yield (1.35 t/ha) followed by Nimbicidine (1.15 t/ha), Spinosad (1.10 t/ha) and Sabion (1.00 t/ha) whereas Cypraplus treated plots provided lowest yield (0.9 t/ha). In terms of reducing aphid population thus plant infestation and increasing yield, all biorational insecticides performed better than conventional insecticides, however, concerning effect on ladybirds and honey bees, only Lufenuron and Nimbicidine can be recommended to farmers.J Bangladesh Agril Univ 22(3): 335-341, 2024